Electric vehicle charging station using fuel cell technology: Two different scenarios and thermodynamic analysis. (November 2021) - Pourrahmani, Hossein; Gay, Martin; Van herle, Jan
Abstract: This study evaluates two different scenarios of an integrated system to generate electricity for a charging station using proton exchange membrane fuel cell (PEMFC) and solid oxide fuel cell (SOFC). To improve the efficiency, the exhaust heat of these two fuel cells are recovered by two different bottoming power cycles of Kalina Cycle (KC) and Organic Rankine Cycle (ORC). The system is designed for a 100 kW charging station capable to charge five cars simultaneously, assuming a standard car used in daily life with a battery capacity of 36 kWh and a range of 220 km. Thermodynamic analysis of the system is performed in different current densities from 0.5 A/cm 2 to 0.8 A/cm 2 . In the first scenario, results indicated that the overall energy efficiency of the system is 58.47% at 0.5 A/cm 2 and 49% at 0.8 A/cm 2, while that of the second scenario is 43.21% at 0.5 A/cm 2 and 35% at 0.8 A/cm 2 . To improve the dynamic response of the system, a high capacity battery and a supercapacitor were integrated to the fuel cell system. It was found that a hybrid combination of the battery and supercapacitor improve the performance of the system.